Isoniazid poisoning: Pharmacokinetics and effect of hemodialysis in a massive ingestion. Issue 4 (16th March 2015) - Skinner, Kirsty; Saiao, Ana; Mostafa, Ahmed; Soderstrom, Jessamine; Medley, Gregory; Roberts, Michael S.; Isbister, Geoffrey K.
Abstract Isoniazid is a rare overdose that causes seizures and there is limited evidence to guide treatment. We report a 20‐year‐old female migrant who presented with recurrent seizures after ingesting 25 g of isoniazid. She was treated with activated charcoal, repeated doses of midazolam for the seizures, and given multiple doses of pyridoxine (14 mg), limited by availability. She was admitted to intensive care, and 5.5 hours post‐ingestion, she was commenced on continuous veno‐venous hemodiafiltration (CVVHDF). She was extubated after 24 hours and CVVHDF was ceased 6 hours later (30 hours post‐overdose). Her renal function remained normal and her initial lactate was the highest at 2.3. She made a full recovery. Five plasma samples were collected before, during, and after CVVHDF, and isoniazid was quantified with liquid chromatography‐tandem mass spectrometry. A pharmacokinetic analysis of time‐isoniazid concentration data was fitted to a two‐compartment model with first‐order input (with fixed ka) with the effect of CVVHDF modeled as a time‐dependent covariate. This suggested that there was initially good clearance with CVVHDF (4 times endogenous clearance), which rapidly declined within hours.